Rational buying motive and emotional buying motive of consumers in the era of Covid-19 pandemic - Aji, Tony Seno; Indrarini, Rachma; Nikmah, Choirul (Technium Social Sciences Journal, 2021)
Currently, the world is experiencing a Covid-19 pandemic outbreak, including Indonesia. Since March 2020 the number of Indonesia's population who has been confirmed positive has increased sharply. This has an impact on changes in the social, cultural, economic and religious structures. The biggest impact was seen in the economic sector, where many companies suffered losses due to decreased purchasing power. People experience consumption behaviour changes during a pandemic, namely panic buying for certain goods-medical equipment and necessities. This research aims to analyse the effect of rational buying motive and emotional buying motive on purchase intention of consumer goods products during the Covid 19 pandemic. This study uses a quantitative method using multiple linear regression. This study found that rational buying motive positively affects purchase intention of products of convenience goods, while emotional buying motive does not affect. In general, people in urban areas still have a rational buying motive in purchasing daily necessities during the pandemic era.